Prognostic Value of Creatine Phosphate and Inflammatory Markers for Mitral Valve Replacement: A Systematic Review and Meta-Analysis - Yanhui Zhu; Chengwei Zou; Jun Zhang; Lei Chen; Yanting Jia (Applied Bionics and Biomechanics)
Purpose. The prognosis of mitral valve replacement is an important clinical issue and may produce unexpected mortality rates if not properly addressed. The postoperative examination results have important prognostic implications. This study was designed to determine the prognostic value of phosphocreatine and inflammatory markers after mitral valve replacement. Method. Comparison and analysis of the data obtained using SPSS software. The computer retrieved PubMed, Science Citation Index (SCI), Embase, VIP, CNKI, CBM, and Wanfang database and manually retrieved randomized controlled trials (RCTs) published at home and abroad on the central muscle protection role of creatine phosphate in heart valve replacement, and the search period was established until February 2018. Two random literature reviewers independently screened the literature and extracted data, using Review Manager (RevMan) (Computer program), version 5.3 (The Nordic Cochrane Centre, The Cochrane Collaboration, Copenhagen, 2014). RevMan software version 5.0 assesses the risk of bias for inclusion in studies. The software performs a meta-analysis of the obtained data. Results. Ten RCTs with a total of 464 participants were enrolled. The meta-analysis results showed that (1) elevated creatine kinase levels often predict a better prognosis after mitral valve replacement (RR=1.36, 95% CI: 1.22 to 1.52, P<0.00001), (2) the creatine kinase isoenzyme level in the venous blood of the phosphocreatine group after 24 h of aortic blocking was significantly lower than that in the control group (SMD=−2.90, 95% CI: -5.19 to -0.60, P=0.01), and (3) Troponin I levels were significantly lower in the intravenous creatine group than in the control group 24 h after opening of the aortic block (SMD=−1.49, 95% CI: -2.02 to -0.97,P<0.00001). Conclusions. Creatine phosphate and inflammatory factor have good predictive value for the prognosis of mitral valve replacement.